2001
DOI: 10.1021/ma0016477
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Morphological Studies of Isotactic Polypropylene Fibers during Heat/Draw Deformation by in-Situ Synchrotron SAXS/WAXD

Abstract: On-line studies of structural and morphological changes during the heating and drawing process of isotactic polypropylene (iPP) fiber were carried out using synchrotron small-angle X-ray scattering (SAXS) and wide-angle X-ray diffraction (WAXD) techniques. A unique image analysis method was used to deconvolute the two-dimensional (2D) WAXD patterns into quantitative fractions of crystal, mesomorphic, and amorphous phases. Results showed that the R-form crystals were quite defective in the initial iPP fibers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(167 citation statements)
references
References 36 publications
7
160
0
Order By: Relevance
“…As time elapsed, the broad diffraction became more asymmetric, and after 0.75 ms, the intensity of α-phase diffractions increased. This phenomenon in iPP-II partially corresponds to those reported by some researchers [26,27], who found that drawing at room temperature transformed the α-phase into the mesophase. The formation of the mesophase occurs through destruction of the lamellar crystalline phase; i.e., lamellar fragmentation, by pulling chains out from crystals.…”
Section: Fiber Temperaturesupporting
confidence: 87%
See 2 more Smart Citations
“…As time elapsed, the broad diffraction became more asymmetric, and after 0.75 ms, the intensity of α-phase diffractions increased. This phenomenon in iPP-II partially corresponds to those reported by some researchers [26,27], who found that drawing at room temperature transformed the α-phase into the mesophase. The formation of the mesophase occurs through destruction of the lamellar crystalline phase; i.e., lamellar fragmentation, by pulling chains out from crystals.…”
Section: Fiber Temperaturesupporting
confidence: 87%
“…Several researchers suggested that the mesophase contains oriented bundles of helical chains with random helical hands [2,26] and is composed of microcrystals of the α-phase [34]. Accordingly, in iPP-I, we assumed that the helical chains of the initial mesophase most likely became oriented with elapsed time after necking, and after 1.0 ms, small-sized microcrystals were organized and formed the oriented α-phase.…”
Section: Waxd Analysesmentioning
confidence: 91%
See 1 more Smart Citation
“…Q is already normalized with respect to the irradiated volume, because of the respective normalization of the measured intensity. Because the major fraction of the studied materials is semi-crystalline HDPE, the predominant contribution [24,[27][28][29][30] to the invariant…”
Section: Scattering Patternsmentioning
confidence: 99%
“…The objective of using eq 2 is only to obtain a qualitative evaluation of the oriented structures (detectable by transmission SAXS) induced by step shear. The unoriented component of the total intensity, I iso [ ], can be obtained with the halo method, 33 which can be described as follows. A series of azimuthal scans are extracted along the scattering vector initiated from the center of the SAXS image.…”
Section: Effect Of the Poss Concentration In Shearmentioning
confidence: 99%